PENGARUH WAKTU PENGASAPAN YANG BERBEDA TERHADAP KARAKTERISTIK KADAR AIR DAN SENSORI IKAN TONGKOL ASAP - Febriadi, Deni; Jumsurizal, Jumsurizal; A, Sri Novalina (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2024)
Smoking is a processing method that combines the drying process withthe provision of natural chemical compounds obtained from thecombustion of natural fuels. This process is influenced by various factors,including the generally high smoking temperature and time. This studywas conducted in three different smoking times with six fish samples. Thesmoking times were 60 minutes (D1), 80 minutes (D2), and 100 minutes(D3). The tests carried out included water content analysis andsensory/organoleptic assessment. Sensory assessment considers four mainquality aspects, including taste, color, aroma, and texture. The resultsshowed that smoked tuna with a smoking treatment of 100 minutes wasthe best treatment with the lowest water content value and the highestoverall organoleptic assessment.